Optimalisasi Penetapan Embarkasi Haji dalam Rangka Efisiensi Biaya Penyelenggaraan Ibadah Haji (BPIH) - Winda, Syahdu; Indriastuti, Dwi; Ferdinand, Julius; Suprayogi, Suprayogi (Komisi Pemberantasan Korupsi, 2020)
Hajj pilgrimage cost (Biaya Penyelenggaraan Ibadah Haji/BPIH) requires around IDR 14 trillion every year. BPIH consists of direct and indirect costs, in which the largest cost component is the airfare reaching 86% of pilgrim deposits in 2019. This study shows that there is BPIH inefficiency that is caused by the disorganized appointment of the embarkation points and the division of flight groups that does not optimize aircraft capacity and airport capabilities. Through the operation research approach, this study models optimization BPIH by determining regional allocations of the pilgrims to embarkation points. The study aims to provide an alternative decision making for the Ministry of Religion in implementing an embarkation zoning policy so that BPIH becomes more efficient, transparent, and free from corruption.